Anxiety and Depression in Drug-Dependent Patients with Cluster C Personality Disorders - Roncero, Carlos; de Miguel, Adelia; Fumero, Ascensión; Abad, Alfonso C.; Martín, Rita; Bethencourt, Juan Manuel; Grau-López, Lara; Rodríguez-Cintas, Laia; Daigre, Constanza (Frontiers in Psychiatry, 2018)
Objective Comorbidity between personality disorders (PD) and substance-use disorders (SUD) is one of the most common findings in the psychiatric field. The patients with Cluster C disorders present maladjustment traits often characterized by high levels of anxiety. The main aim of this study was to find evidences about higher anxiety and depression prevalence on Cluster C than others Clusters, analyzing similarities and differences within, with other Cluster A and B PD patients and patients without PD. Method A total of 822 substance dependent patients (ages18–78; Mean = 38.35, SD = 10.14) completed the structured clinical interview for DSM-IV Axis I and Axis II disorders, Beck Depression Inventory, and State-Trait Anxiety Inventory. Results Results supported poly-consumption in Cluster C patients, being greater alcohol consumption as well as abuse of both stimulants and depressants. Anxiety and depression did not show just one pattern for all patients with SUD-Cluster C PD. There was a relation between anxiety and depression for all the groups except for the Dependent-PD. Conclusion Interventions should focus on aspects like depression and anxiety more than on the substance consumed.